Angiotensin‐converting enzyme 2 rs2285666 polymorphism and clinical parameters as the determinants of COVID‐19 severity in Iranian population. (27th August 2022) - Khalilzadeh, Fereshteh; Sakhaee, Fatemeh; Sotoodehnejadnematalahi, Fattah; Zamani, Mohammad Saber; Ahmadi, Iraj; Anvari, Enayat; Fateh, Abolfazl
Abstract: Host genetic factors may be correlated with the severity of coronavirus disease 2019 (COVID‐19). Angiotensin‐converting enzyme 2 (ACE2) plays a vital role in viral cell entrance. The current study aimed to evaluate the association of ACE2 rs2285666 polymorphism and clinical parameters with COVID‐19 mortality. The ACE2 rs2285666 polymorphism was genotyped using the polymerase chain reaction‐restriction fragment length polymorphism in 556 recovered and 522 dead patients. In this study, the frequency of ACE2 rs2285666 CC was significantly higher than TT genotype in dead patients. The multivariate logistic regression analysis results showed that the higher levels of alanine aminotransferase, alkaline phosphatase, creatinine, erythrocyte sedimentation rate, and C‐reactive protein and the low levels of uric acid, cholesterol, low density lipoprotein, 25‐hydroxyvitamin D, real‐time PCR Ct values, and ACE2 rs2285666 CC genotype were associated with increased mortality rates after COVID‐19. In conclusion, our findings demonstrated a possible link between COVID‐19 mortality, clinical parameters, and ACE2 rs2285666 CC. Further research is required to confirm these results.